NMDA receptor agonists reverse impaired psychomotor and cognitive functions associated with hippocampal Hbegf-deficiency in mice. Issue 1 (December 2015) - Sasaki, Keita; Omotuyi, Olaposi; Ueda, Mutsumi; Shinohara, Kazuyuki; Ueda, Hiroshi
Abstract Background Structural and functional changes of the hippocampus are correlated with psychiatric disorders and cognitive dysfunctions. Genetic deletion of heparin-binding epidermal growth factor-like growth factor (HB-EGF), which is predominantly expressed in cortex and hippocampus, also causes similar psychiatric and cognitive dysfunctions, accompanying down-regulated NMDA receptor signaling. However, little is known of such dysfunctions in hippocampus-specificHbegf cKO mice. Results We successfully developed hippocampus-specific cKO mice by crossbreeding floxedHbegf andGng7-Cre knock-in mice, asGng7 promoter-driven Cre is highly expressed in hippocampal neurons as well as striatal medium spiny neurons. In mice lacking hippocampusHbegf gene, there was a decreased neurogenesis in the subgranular zone (SGZ) of the dentate gyrus as well as down-regulation of PSD-95/NMDA-receptor-NR1/NR2B subunits and related NMDA receptor signaling. Psychiatric, social-behavioral and cognitive abnormalities were also observed in hippocampal cKO mice. Interestingly, D-cycloserine and nefiracetam, positive allosteric modulators (PAMs) of NMDA receptor reversed the apparent reduction in NMDA receptor signaling and most behavioral abnormalities. Furthermore, decreased SGZ neurogenesis in hippocampal cKO mice was reversed by nefiracetam. Conclusions The present study demonstrates that PAMs of NMDA receptor have pharmacotherapeutic potentials to reverse down-regulated NMDA receptor signaling, neuro-socio-cognitive abnormalities and decreased neurogenesis in hippocampal cKO mice.